2016
DOI: 10.2176/nmc.cr.2015-0351
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Cerebral Infarction Caused by Bow Hunter’s Syndrome during Sport: Two Case Reports

Abstract: We report two cases of juvenile cerebral infarction caused by bow hunter’s syndrome (BHS) during sport. Case 1 was a 17-year-old male who developed a partial visual field defect after playing basketball. BHS was diagnosed because cervical ultrasonography demonstrated occlusion of the vertebral artery when the neck was rotated. After C1–2 posterior fixation was performed, his symptoms resolved. Case 2 was an 18-year-old male with recurrent visual disturbance after playing handball. Cerebral infarction occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…20 Additional treatment options include vertebral artery sacrifice, which is not supported by literature nor recommended by this article, or vertebral artery stenting. Two cases in our table used vertebral artery stenting, but one of these 8 went on to require fusion. For the other patient, on long-term follow-up both stents were found to be sheared with complete occlusion of both vertebral arteries and muscular branch collateralization reconstituting V3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Additional treatment options include vertebral artery sacrifice, which is not supported by literature nor recommended by this article, or vertebral artery stenting. Two cases in our table used vertebral artery stenting, but one of these 8 went on to require fusion. For the other patient, on long-term follow-up both stents were found to be sheared with complete occlusion of both vertebral arteries and muscular branch collateralization reconstituting V3.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients had recurrence after the last reported treatment, but length of follow-up varied. Several patients 4,5,8 started with medical therapy but were taken for surgical intervention when medication failed to prevent recurrent stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Post hoc tests identified four homogenous subsets with regard to age: golf players were significantly older than participants of football, basketball, and combat sports; football players were also significantly younger than runners, tennis players, and people engaging in exercise/weight lifting and scuba diving (Figure 1(a)). The proportion of female patients also differed significantly 36 1 À Springboard diving 37 1 À Wakeboarding 38 1 À Waterskiing 39 1 À Surfing 40 1 À Kitesurfing 41 1 À Running/jogging 22 129 3 À Handball 74 1 À Hockey 78 1 À Paddle bal 40 1 À Bowling 84 1 À a Indicates which types of sports are included in between-group analyses (all groups with at least 10 cases). 'Yes': forming a main group, '(þ)': part of main group, 'À': not included in further analysis, '/': some of its constituents are included in between-group analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The cause was identified as stenosis caused by hyper-rotation apophyseal joint subluxation. 9 Missori et al 17 reported on a case of atlantoaxial rotatory subluxation resulting in transient blindness after a neck injury. A limited number of published studies cite ultrasonography as a valuable assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Transient vision loss (TVL) and blindness have also been reported in some cases. 4,5,[7][8][9] Bow hunter syndrome studies are limited to case studies and case series. The largest overview of BHS to date was published by Jost and Daily 7 in 2015, in which 126 cases were described and categorized and in which a variety of causes, sites of stenosis, and treatment regimens are described.…”
Section: Introductionmentioning
confidence: 99%